Imaging of radiocarbon-labelled tracer molecules in neural tissue using accelerator mass spectrometry. - Hedges, R; Jiang, Z; Bronk Ramsey, C; Cowey, A; Roberts, J; Somogyi, P (Nature Publishing Group, 1996)
Autoradiography is widely and successfully used to image the distribution of radiolabelled tracer molecules in biological samples. The method is, however, limited in resolution and sensitivity, especially for 14C. Here we describe a new method for imaging 14C-labelled tracers in sections of biological tissue. A highly focused beam of gallium ions bombards the tissue, which is eroded (sputtered) into constituent atoms, molecules and secondary ions. The 14C ions are detected in the secondary beam by the most sensitive method available, namely accelerator mass spectrometry. The specimen is scanned pixel by pixel (1 x 2 microm), generating an image in a manner analogous to scanning electron microscopy. The method can thus be regarded as a specialized form of scanning secondary ion mass spectrometry (SIMS), referred to here as SIAMS (ref. 2). We have used SIAMS to localize the neurotransmitter gamma-aminobutyric acid (GABA) in thin sections of cerebral cortex, and show that it can generate 14C images that are much improved on 14C autoradiography. A scan takes 10-20 min and reveals individual axons, neurons and glial cells at high sensitivity. In principle, the resolution could be increased by up to tenfold, and the method could be extended to some other nuclides.